INVESTIGATION BY NUMERICAL MODELING OF INFLUENCE OF THE SHAPE OF DEFORMING ZONE OF DIE AT WIRE DRAWING OF STEEL HIGH-CARBON WIRE ON TEMPERATURE AND MODE OF DEFORMATION IN WIRE AND DIE - Ju. L. Bobarikin; M. N. Vereshchagin; M. Ju. Tseluev; A. V. Vedeneev; O. I. Ignatenko (Литьë и металлургия)
Investigation by numerical modeling of influence of the form of deforming zone of die at drawing of steel highcarbon wire on temperature and strained-deformed state in wire and die is carried out.